Gustatory, olfactory, and visual convergence within the primate orbitofrontal cortex - Rolls, ET (J Neurosci, 1994)
Behavioral and perceptual responses to food depend on a convergence between gustatory, olfactory, and visual information. In previous studies a secondary cortical taste area has been found in the caudolateral orbitofrontal cortex of the primate. Furthermore, neurons with olfactory responses have been recorded in a more medial part of the orbitofrontal cortex, and visual inputs have been shown to influence neurons in an intermediate region. These studies suggest that the orbitofrontal cortex may act as a region for convergence of multiple sensory modalities including chemosensation. In the present study neurons throughout the caudal two-thirds of the orbitofrontal cortex of the macaque were tested to gustatory, to olfactory, and to visual stimulation to investigate whether convergence occurs. Neurons in this region of cortex were found that responded to stimulation of the taste, olfactory, or visual system. In addition, some neurons were found with bimodal responses, responding for example to both taste and olfactory, or taste and visual stimuli. Since these multimodal neurons were found in very close proximity to unimodal neurons, and the unimodal sensory neurons were intermingled, it is possible that the orbitofrontal cortex represents the first cortical area of convergence for these three modalities in primates.